Mediastinal mass in clinical practice - N. G. Poteshkina; A. A. Troshina; M. Y. Maslova; M. A. Lysenko; I. V. Samsonova; E. I. Zhelnova (Медицинский совет, 2018)
Mediastinal masses include a wide range of both benign and malignant diseases. Current evidence shows that they constitute 3–7% of all oncological diseases, with primary tumours (thymoma, lymphoma, germ cell tumours) accounting for 3% of all mediastinal masses. Lymphoma and thymoma, for instance, are the most common, while germ cell tumours are of much less frequent occurrence. Neurogenic tumours, it bears noting, are also widespread making up 12–21% of all mediastinal masses, predominantly so among paediatric population. Morphologically 25–49% of all masses are malignant. The rationale of the subject matter is the fact that statistics for progress of the disease masked as other conditions have been on the rise. It is noted that about 60% of mediastinal masses manifest themselves in classical respiratory symptoms, while the rest of cases are represented by a variable clinical picture, which makes it more difficult to diagnose and decide on the therapeutic approach. The article presents a clinical case of a 32-year-old female patient diagnosed as primary mediastinal large B-cell lymphoma which made its first appearance as a clinical picture of respiratory complaints. This clinical case describes the  diagnosis algorithm using up-to-date laboratory and instrumental methods.